(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This research explores the possibilities of energy recovery and environmental impact reduction through pyrolysis processing of gas-chemical industry waste. The study focuses on obtaining alternative fuels from waste using modern thermochemical technologies and reducing greenhouse gas emissions.